EXAMINING THE PRODUCTIVITY BIAS HYPOTHESIS FOR NEXT 11 COUNTRIES - Gülfer Vural (Sosyal Ekonomik Araştırmalar Dergisi, 2020)
One of the reasons of deviation from Purchasing Power Parity is the Productivity Bias Hypothesis (PBH) that is also known as Balassa-Samuelson Hypothesis which is based on Balassa (1964) and Samuelson (1964). Productivity Bias Hypothesis implies that productivity causes a real appreciation in currency of a relatively more productive country. Mechanism can be briefly summarized as follows: Productivity increase in tradable sector increases wages in this sector and due to labor mobility across sectors wages in non-tradable sectors rise. Then, prices increase and finally exchange rates rise. Due to relatively high growth rates and productivity increases emerging countries can be good samples to investigate the hypothesis. The purpose of this study is to investigate the validity of Productivity Bias Hypothesis for Next 11 countries (Bangladesh Egypt, Indonesia, Iran, South Korea, Mexico, Nigeria, Pakistan, Phillipines, Turkey and Vietnam). Autoregressive Distributed Lag method (ARDL) of cointegration is used to analyze time series data. Empirical results suggest that the hypothesis is supported in Bangladesh, Indonesia, Turkey and Vietnam for the considered period of time. The policy implications are provided as well.